Pengaruh Pupuk Organik Cair Gedebog Pisang Terhadap Pertumbuhan dan Hasil Beberapa Jenis Tanaman Sayur - Analisa, Widya; Annisa, Febrina Nur (Universitas Methodist Indonesia, 2024)
The presence of banana stems (gedebog pisang) in Lubuklinggau City is often considered waste and is easily found. Processing banana stems is rarely practiced by the local community. The production of liquid organic fertilizer (LOF) from banana stems aims to utilize this waste into something beneficial, particularly for vegetable crops. This study aims to investigate the effect of LOF made from banana stems on the growth and yield of several vegetable plants, such as water spinach (Ipomoea reptans Poir), green spinach (Amaranthus hybridus L), and mustard greens (Brassica juncea L). It also seeks to determine the impact of banana stem LOF on soil pH. The study employed a Randomized Block Design (RBD) with the following treatments: P0 – control (no fertilizer), P1 – base fertilizer NPK Mutiara 17:17:17, and P2 – banana stem LOF. The results indicated that the application of banana stem LOF (P2) influenced plant growth, including plant height and the number of leaves in water spinach, green spinach, and mustard greens. The effects of banana stem LOF were comparable to those of the synthetic NPK Mutiara fertilizer.